1992
DOI: 10.1007/bf00376435
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, body temperature and hormonal responses to repeated periods of prolonged cycle-ergometer exercise in men

Abstract: This study was designed to find out whether rest intervals and prevention of dehydration during prolonged exercise inhibit a drift in metabolic rate, body temperature and hormonal response typically occurring during continuous work. For this purpose in ten healthy men the heart rate (fc), rectal temperature (Tre), oxygen uptake (VO2), as well as blood metabolite and some hormone concentrations were measured during 2-h exercise at approximately 50% maximal oxygen uptake split into four equal parts by 30-min res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…It is possible that circulating substrate (free fatty acids or glucose) was still available from the ®rst bout of exercise. Kaciuba-Uscilko et al (1992) observed increases in free fatty acid and glycerol concentrations (with reductions in glucose) in response to four 30-min bouts of exercise at 50% O 2max , each separated by 30-min recovery periods.…”
Section: Discussionmentioning
confidence: 83%
“…It is possible that circulating substrate (free fatty acids or glucose) was still available from the ®rst bout of exercise. Kaciuba-Uscilko et al (1992) observed increases in free fatty acid and glycerol concentrations (with reductions in glucose) in response to four 30-min bouts of exercise at 50% O 2max , each separated by 30-min recovery periods.…”
Section: Discussionmentioning
confidence: 83%
“…1d), the negative feedback mechanism might operate in the reduction in GH response to a subsequent resistance exercise. On the other hand, Kaciuba-Uscilko et al (1992) showed that four bouts of 30-min aerobic exercise separated by a 30-min rest period cause similar GH responses to all bouts, even though the GH concentration did not return to its pre-exercise level at the beginning of a subsequent bout. Kanaley et al (1997) demonstrated that the GH response to high-intensity aerobic exercise is augmented with repeated exercise.…”
Section: Discussionmentioning
confidence: 95%
“…This response is thought to be related to the overriding nonthermal influence on core temperature regulation associated with the work/rest transitions (219,243). In support of this hypothesis, it has been shown that intermittent exercise results in a progressive increase in core temperature although the magnitude of increase in the postexercise elevation in core temperature is reduced with successive work/rest intervals (219,(243)(244)(245)(246)(247).…”
Section: Calorimetic Evidence For Nonthermal Modulation Of Whole-bodymentioning
confidence: 94%